2020
DOI: 10.3390/s20030749
|View full text |Cite
|
Sign up to set email alerts
|

Stray Flux Sensor Core Impact on the Condition Monitoring of Electrical Machines

Abstract: The analysis of the stray flux for electrical machine condition monitoring is a very modern and active research topic. Thanks to this technique, it is possible to detect several types of failures, including stator and rotor inter-turn faults, broken rotor bars and mechanical faults, among others. The main advantages are that it involves a non-invasive technique and low-cost monitoring equipment. The standard practice is to use coreless flux sensors, with which the stray flux of the machine is not perturbed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
0
6
0
2
Order By: Relevance
“…This technique requires a phase angle determination and some motor parameters to estimate the torque with a good accuracy. Note that the cited method applied a coreless flux sensor, being the induced voltage in this type of core very low and quite similar, in some cases, to the amplitude of the noise floor, as mentioned by [14]. As described by [12], other studies have shown the use of internal sensor for condition monitoring of rotating electrical machines [15,16].…”
Section: Introductionmentioning
confidence: 83%
“…This technique requires a phase angle determination and some motor parameters to estimate the torque with a good accuracy. Note that the cited method applied a coreless flux sensor, being the induced voltage in this type of core very low and quite similar, in some cases, to the amplitude of the noise floor, as mentioned by [14]. As described by [12], other studies have shown the use of internal sensor for condition monitoring of rotating electrical machines [15,16].…”
Section: Introductionmentioning
confidence: 83%
“…The total dimensions are 60x25x40 mm (length x width x height) and it had 200 turns. Further information about this flux sensor are detailed in [20]. The first set of starting tests were performed with the machine unloaded, that is the induction machine stator was disconnected.…”
Section: Methodsmentioning
confidence: 99%
“…Monitoring magnetic flux has become a widespread and effective method for fault detection in electrical machines, as many early failures create a magnetic asymmetry that can be detected [86]. Electromagnetic measurement can be efficiently used to monitor the electrical machine as an additional or alternative tool to stator current monitoring.…”
Section: Electrical and Electromagnetic Monitoringmentioning
confidence: 99%